Analisis Pengaruh Jumlah Penduduk, Tingkat Pengangguran dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Kabupaten Malang - Cindy Fatikha Sari; Syamsul Huda (Al-Buhuts, 2023)
This research was conducted with the aim of knowing the effect of population, unemployment and economic growth on the poverty rate in Malang district from 2007 to 2021. The data used in this research is secondary data from the Central Bureau of Statistics (BPS) in Malang district. The research method used is a quantitative method using multiple linear regression analysis. Thus, the results achieved simultaneously on population, unemployment rate and economic growth jointly affect the poverty rate, while some population variables have a negative impact on the poverty rate, the unemployment rate has a positive impact on the poverty rate, and economic growth has a positive impact on poverty rate in Malang Regency